2014
DOI: 10.1039/c4en00079j
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the properties and applications of nanoceria: is there still plenty of room at the bottom?

Abstract: Nanoceria is an exceptionally versatile, commercially valuable catalytic material whose properties vary dramatically from that of the bulk material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
182
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(190 citation statements)
references
References 89 publications
3
182
0
5
Order By: Relevance
“…Cerium oxide nanoparticles (nCeO 2 ) are widely utilized in catalytic applications, mechanical planarization, and fuel additives (Reed et al 2014). Modeling studies have predicted that nCeO 2 could contaminate agricultural lands through biosolid application (Keller et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Cerium oxide nanoparticles (nCeO 2 ) are widely utilized in catalytic applications, mechanical planarization, and fuel additives (Reed et al 2014). Modeling studies have predicted that nCeO 2 could contaminate agricultural lands through biosolid application (Keller et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…: CeO 2 , ceria, cerium oxide) as one of the most abundant rare earth oxides has prompted research on the synthesis and development of functional ceria nanoparticles. As a result, nanoceria is increasingly used in a variety of industrial and commercial applications, including catalysis 1, 2 , e.g., as a diesel fuel additive to increase fuel combustion efficiency and decrease soot emissions 3, 4 ; in chemical mechanical planarization/polishing 5 ; UV-shielding 6 ; in semiconductors; in toner formulations 7 ; and as an additive in various nanocomposites, as reviewed 8 . The inevitable increase in consumer and occupational exposures raises the need for a comprehensive toxicological characterization of nanoceria 9 .…”
Section: Introductionmentioning
confidence: 99%
“…[27] It was furthermore shown that the smaller the size of the nanoceria particles, the higher the amount of Ce 3+ and hence that of oxygen defects in the structure and on the surface of the particles. [7] …”
Section: Protective Effects Of Ceria Materialsmentioning
confidence: 99%
“…[7] Nanoceria is a promising material for energy-related applications such as in fuel cells, hydrogen production and purification, and water splitting. [8] Its use in three-way catalysts, especially as the mixed oxide, CeO 2 -ZrO 2 , in motor vehicles, has proven very valuable for environmental issues, as it reduces the emission of polluting gases by controlling the air-to-fuel ratio thanks to its oxygen-storage capacity.…”
Section: Introductionmentioning
confidence: 99%